The Variation of Pulp Canal Configuration in Mandibular Posterior Teeth Using Cone Beam Computed Tomography in Indonesia Subpopulation Mongoloid Race: Konfigurasi Saluran Akar pada Gigi Posterior Mandibula Melalui Cone Beam Computed Tomography pada Ras Mongoloid Indonesia - Boel, Trelia; Kartika, Dewi; Dennis (Dentika: Dental Journal, 2020)
It is important to understand pulp canal configuration to have a successful endodontic treatment. Cone Beam Computed Tomography (CBCT) radiography is able to assess the pulp canal configuration, especially on the lingual/palatal, compared to the periapical radiography. The objective of the research is to know the prevalence pulp canal configuration of mandibular molar teeth in Indonesia subpopulation Mongoloid race using CBCT radiography. This research is a descriptive survey with a cross-sectional approach, using 38 CBCT radiographs from the patients undergoing dental treatments in hospitals in Medan. The subjects were selected based on research criteria; then their CBCT radiographs were interpreted and analyzed. The result shows the existence of mandibular mesial root type 2-1 (28.94%), 1-2-1 (5.26%), 2-2 (55.26%), 2-1-2-1 (2.64%), 3-2 (5.26%), 3-1 (2.64%), distal root type 1-1 (36.84%), 2-1 (23.68%), 1-2-1 (15.79%), 1-2 (2.63%), 2-2 (13.17%), 2-1-2-1 (5.26%), 1-3-1 (2.63%). The distolingual root of mandibular first molars consisted of type 1-1 (100%). Mesial root of mandibular second molars of type 1-1 (2.63%), 2-1 (50%), 1-2-1 (5.26%), 2-2 (36.85%), 2-1-2-1 (2.63%), 1-2-1-2 (2.63%), distal root type 1-1 (57.89%), 2-1 (15.79%), 1-2-1 (13.16%), 2-2 (10.53%), 2-1-2 (2.63%). This variation of the pulp canal can be influenced by the shape of roots. A flat root usually contains pulp canal configuration type II “ VIII Vertucci, similarly to mandibular molar mesial canals. As a summary, there is a variation of pulp canal configuration in mandibular first and second molars on Indonesian Mongoloid race, as seen from the CBCT radiographs.